2012
DOI: 10.1093/jpids/pis070
|View full text |Cite
|
Sign up to set email alerts
|

Noroviruses: The Most Common Pediatric Viral Enteric Pathogen at a Large University Hospital After Introduction of Rotavirus Vaccination

Abstract: We conducted an 8.5-year study examining enteric viruses at Texas Children's Hospital (TCH) before and after rotavirus vaccine introduction. Norovirus prevalence was 10.9%. Rotavirus prevalence decreased 64% after vaccine licensure. Noroviruses are the most common TCH enteropathogen and will likely eclipse rotaviruses as the most important US pediatric gastroenteritis pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 9 publications
11
106
2
Order By: Relevance
“…Our NGS data did not reveal the presence of norovirus, a leading cause of pediatric gastroenteritis (69,70,77,78), in any of the neonatal stool samples analyzed in this study. This finding was unexpected given an earlier surveillance study indicating that a third of all norovirus-infected Vellore neonates with GI disease were coinfected with RV (79).…”
Section: Discussioncontrasting
confidence: 63%
“…Our NGS data did not reveal the presence of norovirus, a leading cause of pediatric gastroenteritis (69,70,77,78), in any of the neonatal stool samples analyzed in this study. This finding was unexpected given an earlier surveillance study indicating that a third of all norovirus-infected Vellore neonates with GI disease were coinfected with RV (79).…”
Section: Discussioncontrasting
confidence: 63%
“…The TCH-060 strain of NoV used in our studies was isolated from an 11-year-old boy in 2003 at the Texas Children's Hospital, Houston, TX (43). Phylogenetic analysis of the VP1 amino acid sequence (GenBank accession number AEQ77282.1) confirmed that it belonged to the GI.7 genotype and showed that it is distant from the structurally characterized GI.1 and GI.2 strains (data not shown).…”
Section: Resultsmentioning
confidence: 82%
“…In the United States alone, they annually cause 19-21 million symptomatic infections resulting in up to 71,000 hospitalizations and 800 deaths. 1 In fact, they have become the leading cause of severe childhood diarrhea since the introduction of a successful rotavirus vaccination program 2,3 and they are the predominant cause of foodborne disease outbreaks. 4 In developing countries, HuNoVs are likely even more devastating, an idea underscored by an estimate that they cause over a million clinic visits and 200,000 fatalities in young children in impoverished parts of the globe.…”
Section: Introductionmentioning
confidence: 99%